Seismic Performance Evaluation of Prefabricated Shear Wall Structure with Rabbet-Unbonded Horizontal Connection - Chongfang Sun; Zhiqiang Zhao (Advances in Civil Engineering)
This paper is concerned about seismic performance evaluation of precast shear wall structure with Rabbet-unbonded Horizontal Connection (RHC). RHC is composed of rabbets and unbonded rebar segments. The rabbets are used to improve the shear capacity and prevent slippage of connection, and the unbonded rebar segments are used to improve the ductility and energy dissipation. The constitutive relation of unbonded region is put forward and verified, which is applied in RHC shear wall structure model. The pushover analysis, capacity spectrum analysis and seismic performance evaluation of RHC shear wall structure are performed, which are compared with that of conventional connection shear wall structure and cast-in-place shear wall structure. The result shows that RHC shear wall structure reaches basic seismic fortification target of “no damage in small earthquake, repairable in moderate earthquake, no collapse in severe earthquake,” and basically reaches the seismic performance of cast-in-situ shear wall structure. Finally the effect of unbonded length and unbonded level on storey drift and interlayer drift angle are analyzed and the design proposal is put forward.